Multimodal imaging findings of primary renal well-differentiated neuroendocrine tumors (carcinoid): a case report and literature review - Wei, Bangcheng; Chen, Yuge; Chen, Yueqin; Zhang, Shujun (Frontiers in Oncology, 2026)
Primary renal well-differentiated neuroendocrine tumors (NETs) are rare. Due to their non-specific nature, the detection and monitoring of NETs remain highly challenging. Here, we report a case of a 45-year-old man who was admitted after an incidental finding of a space-occupying lesion in the kidney during a routine physical examination. The patient underwent CT and MRI multimodal imaging, followed by pathological and immunohistochemical analysis after surgery, leading to a diagnosis of well-differentiated renal NET. He was subsequently followed up for a long period. A review of the literature, in conjunction with this case, revealed that these tumors present with non-specific clinical and imaging features. Diagnosis primarily relies on pathological and immunohistochemical evaluation. Well-differentiated renal neuroendocrine tumors are associated with low malignant potential and a favorable prognosis. Surgical resection is the treatment of choice, and long-term follow-up is essential to monitor the patient’s condition. By combining this case with existing literature, we aim to provide valuable insights for clinicians in the diagnosis and management of renal NETs.